Supporting sustainability and healthy learning environment through Smart Green Management System (SGMS) - Abdullah, Salfarina; Hamdan, Hazlina; Anuar, Sazly (IOP Publishing, 2018)
Today, most universities worldwide have initiated the green campus campaign. In line with the campaign intention to sustain and create healthy learning environment, we developed a system, which aims to facilitate the management of recycle program as part of green campus initiative. Smart Green Management System (SGMS) is a mobile crowdsourcing-based system with a capability to help fast-managing and coordinating recycling effort between the green university council and green city council. This system allows access from any mobile devices at anytime and anywhere. Centralized participatory crowdsourcing method is the key approach in developing this system. In this approach, the crowd is tasked with finding and collecting information into a common location and format. It is ideal for information gathering, organization, and reporting problems, which are demonstrated by SGMS.